2013
DOI: 10.1136/annrheumdis-2012-eular.2576
|View full text |Cite
|
Sign up to set email alerts
|

FRI0119 Improvement in some, but not all, surrogate measures of cardiovascular disease following intensive treatment of early rheumatoid arthritis

Abstract: Background Patients with rheumatoid arthritis (RA) have an elevated risk of cardiovascular disease (CVD), predominantly ischaemic heart disease (IHD). Systemic inflammation is thought to be a key contributor to this risk and it is hoped early therapeutic suppression of inflammation will reduce cardiovascular (CV) events in the long term. Insulin resistance, associated with metabolic syndrome, N-terminal pro-brain natriuretic peptide (NT-proBNP) and atherogenic lipid profiles have been proposed as potential sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Data on patients with RA treated with infliximab were obtained from four RCTs (three full-length articles [ 54 56 ] and two conference abstracts [ 57 , 58 ]), 11 PCs (11 full-length articles [ 35 , 59 – 68 ] and one conference abstract [ 69 ]), and five RCs (four full-length articles [ 38 , 49 , 51 , 70 ] and one conference abstract [ 19 ]). Data from several studies showed that treatment with infliximab resulted in significant increase in TC [ 54 , 57 63 , 65 , 67 , 68 , 70 ], HDL-C [ 57 65 ], and TG [ 61 , 63 , 65 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on patients with RA treated with infliximab were obtained from four RCTs (three full-length articles [ 54 56 ] and two conference abstracts [ 57 , 58 ]), 11 PCs (11 full-length articles [ 35 , 59 – 68 ] and one conference abstract [ 69 ]), and five RCs (four full-length articles [ 38 , 49 , 51 , 70 ] and one conference abstract [ 19 ]). Data from several studies showed that treatment with infliximab resulted in significant increase in TC [ 54 , 57 63 , 65 , 67 , 68 , 70 ], HDL-C [ 57 65 ], and TG [ 61 , 63 , 65 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In three PC studies, there was significant increase in LDL-C for at least the first 12 weeks [ 60 , 61 , 64 ], whereas data from two RCTs [ 54 , 57 , 58 ] and two PC studies [ 65 , 67 , 68 ] showed no significant change. Significant improvement in atherogenic index was reported in one RCT [ 57 , 58 ], but significant worsening was reported in three PC studies [ 61 , 63 , 65 ], and no significant change was reported in one RCT [ 56 ] and two PC studies [ 59 , 60 ]. Several studies reported significant reduction in inflammation as determined by decreased CRP levels [ 56 , 60 , 64 , 67 , 68 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation